First report of the tribe Pselaphini from Xizang, with description of two new species (Coleoptera: Staphylinidae: Pselaphinae) - Zhang, Yong-Qin; Pubu, Zhuoma; Yin, Zi-Wei (Zootaxa, 2026)
The tribe Pselaphini is reported to occur in Xizang, with two new species being described from Mêdog and Zayü counties: Pselaphogenius dagmo Zhang & Yin, sp. nov. and Pselaphogenius xizangensis Zhang & Yin, sp. nov. Both taxa can be readily distinguished from all East Asian congeners by their external appearances, in combination with the characteristic aedeagal structures.